Managing our natural resources - Camp, William G.; Daugherty, Thomas B. (Albany, N.Y. : Delmar, 1997)
Examines the nature, history, and management of natural resources ranging from soil and water to forests, wildlife, and marine resources. Includes suggested activities and discussion of occupations in the field.
Includes index.
1
Keywords: Natural resources -- United States -- Management -- Juvenile literature; Natural resources -- Management -- Vocational guidance -- United States -- Juvenile literature; Natural resources -- Management; Conservation of natural resources; Occupations